An Automated DTFWOA-ASI model for Classification and Identification of Speakers utilizing a Metaheuristic Algorithm - T.S. Mullai vendan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Identifying a speaker is a task of classification that aims at recognizing an individual based on sequential data over time. Given that a speech signal manifests as a one-dimensional, continuous time series, most contemporary studies rely on either convolutional neural networks (CNN) or recurrent neural networks (RNN). These techniques have shown effectiveness across various applications, yet efforts to merge these two models for investigating speaker recognition tasks remain unexplored. A spectrogram integrated into a speech signal reveals the voiceprint's spatial attributes, reflecting the voice spectrum. This makes CNN highly suitable for drawing out spatial characteristics, essentially capturing the spectral correlations present in acoustic signatures. Concurrently, with the speech signal being time-sequential, deep RNNs are superior in depicting extended speech compared to more superficial networks. The study introduces a new model named Dual-Tier Feature Extraction with Whale Optimization Algorithm for Automated Speaker Identification (DTFWOA-ASI), designed to address the shortcomings found in earlier models. The DTFWOA-ASI approach is a cutting-edge method designed specifically for the identification of speaker identities. It employs the method of average median filtering (AMF) to remove background noise from sound recordings. Subsequently, the strategy utilizes both MFCC and spectrogram data as inputs into the VGGish model, an advanced deep-learning convolutional network engineered for extracting crucial features. For the fine-tuning of the LSTM-RNN model's hyperparameters, the technique makes use of the Whale Optimization Algorithm (WOA). The approach integrates a long short-term memory network with a recurrent neural network (LSTM-RNN) to enable the automatic identification and classification of speakers. The performance and accuracy of the DTFWOA-ASI framework were thoroughly assessed through several experimental procedures. A comparative analysis highlights the model’s superior performance in comparison to the latest methodologies.